The Hardy-Littlewood Theorem and the Operator of Harmonic Conjugate in Some Classes of Simply Connected Domains with Rectifiable Boundary - Tkachenko, N.M.; Shamoyan, F.A. (Журнал математической физики, анализа, геометрии, 2009)
The analogue of known theorem Hardy-Littlewood about Lp-estimations of derivative analytical function through norm to the function, also are proved Lp-weight estimations the operator of harmonic conjugate in some classes of simply connected domains with rectifiable boundary for all 0 < p < +∞.